Citation of an Academic Research Paper through Use of Software - Meer, Somaiya (Journal of Social Sciences - Kabul University, 2020)
This paper introduces the software Zotero, which assists researchers in easily managing citations. It includes a definition and history of the software, along with instructions on installation and usage. Citation plays a crucial role in academic promotion across all fields of study, and even senior students rely on proper citation for their monographs. This software enables researchers to collect, organize, cite, and share research sources efficiently. Additionally, Zotero can be used for file management, metadata organization, notes, and tagging. Files can be added to the Zotero library either as copies or as links, with original file copies stored in the Zotero data directory. The software allows free storage of up to 100MB, while libraries and IT services provide secure online servers for additional storage. University libraries may assist users in setting preferences for optimal use.